PERAN PEMERINTAH DESA DALAM MENGURANGI KEMISKINAN MELALUI PEMBANGUNAN INFRASTRUKTUR DI DESA SIRNABAYA KABUPATEN KARAWANG - , Gina Laelita Sukma (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
The problem of poverty is a serious problem found in areas, especially in rural areas, but Sirnabaya Village succeeded in reducing the poverty rate in 2018 by 4.5% through infrastructure development using village funds. This research uses Suhardono's theory which aims to examine and analyze the role of village government as facilitator, mobilizer and regulator in infrastructure development. The method of this research is descriptive qualitative by collecting data through interviews and literature study. The results of the research state that the Sirnabaya Village government plays a very important role and contributes and always tries to help its residents who are trapped in poverty so that the Sirnabaya Village government in 2022 will succeed in reducing the poverty rate again to 10%. The Sirnabaya Village government always works together in efforts to improve the welfare of its citizens, especially when dealing with infrastructure that is often used by the public. So far, the Sirnabay Village government has built a lot of infrastructure development which of course has an impact on the residents' income, one of which is road construction and drainage construction.